(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
A revision of the corpus of Palaeohispanic inscriptions from the Southern Central plateau of Spain known to date is provided in this paper, as the basis for analysing which languages were spoken in this area in Antiquity and understanding their geographical and chronological distribution. Some onomastic data (personal names and place-names) are also taken into account for this purpose. On the basis of the epigraphic evidence, including coin legends, it can be stated that the area of diffusion of the Southern Iberian script is larger than previously assumed and reaches further north. This script is now well documented in the Oretan towns to the north of Sierra Morena and in the eastern and western areas of the territory under consideration. The analysis of those inscriptions points to the fact that the Iberian language was employed by the Oretans inhabiting the Southern Central plateau, in the same way as it was by the ones living to the south of Sierra Morena. Celtiberian inscriptions basically appear in a specific area of this territory, mainly in the province of Cuenca and partly in the province of Guada- lajara. Celtiberian epigraphy must be linked to a more recent process of Celtiberization of the northeastern area of the territory under consideration. The Carpetan territory is more difficult to assess from the linguistic point of view, given that Celtic and Iberian elements appear next to each other.